2015
DOI: 10.3126/jonmc.v4i1.13299
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Selection of Permanent Pacemaker Implantation at Manmohan Cardiothoracic Vascular and Transplant Centre, Kathmandu, Nepal

Abstract: Background: Permanent pacemaker implantation is a minimally invasive surgical procedure in the management of patients with cardiac rhythm disturbances. Previous studies have reported gender differences in pacemaker selection. There is lack of evidences in selection of pacemaker mode with respect to gender in Nepal. Therefore, this study was performed to compare the frequency of implantation between men and women.Objectives: This study was performed to compare the frequency of implantation rate between men and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 22 publications
(15 reference statements)
4
3
0
Order By: Relevance
“…Main reason for it was financial constraint and even more so in female probably due to gender bias. Similar results regarding gender related difference was found in study done by Khanal J et al 12 . Study done by Nowak B et al 16 in Germany also showed similar sex differences in dual chamber pacemaker implantation, even more so in old age individuals and in study done by Lamas GA et al in USA 17 , whereas study done by Veerareddy et al 18 in USA showed no sex differences in the selection of pacemaker.…”
Section: Age Groupsupporting
confidence: 89%
See 1 more Smart Citation
“…Main reason for it was financial constraint and even more so in female probably due to gender bias. Similar results regarding gender related difference was found in study done by Khanal J et al 12 . Study done by Nowak B et al 16 in Germany also showed similar sex differences in dual chamber pacemaker implantation, even more so in old age individuals and in study done by Lamas GA et al in USA 17 , whereas study done by Veerareddy et al 18 in USA showed no sex differences in the selection of pacemaker.…”
Section: Age Groupsupporting
confidence: 89%
“…Nepal for the last 20 years, there is no large scale published data of pacemaker implantations. Few studies and reports have been published regarding clinical profile, short term outcome, experiences and gender differences in pacemaker implantation in different centre including MCVTC[9][10][11][12][13] .The objective of this study is to analyze the clinical profile and indications of permanent pacing in Nepali population presenting to Age Distribution of Patients with PPI…”
mentioning
confidence: 99%
“…The trends in the use of more number of single chamber pacemakers as in our study is similar to the other study done at various cardiac centers of our country [3][4][5][6][7] and India. 8 However the trend of implantation of pacemaker in other developed countries at USA 9 and Australia 10 have showed majority of their patients received dual chamber pacemaker.…”
Section: Discussionsupporting
confidence: 88%
“…2 The similar findings has been shown in various study done in our part of the country. [3][4][5][6][7] The mean age of the study population was 65 years which were similar to the other study done at India with mean age of 60.5, 8 In Poland mean age of 63.5 years 12 and similar to the other study done in our country. [3][4][5][6][7] However in other registries and the 11 th world survey mean age ranged from 65 to 80 years in patients who underwent PPM implantation.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation